Studies on the thermal decomposition of multiwall carbon nanotubes under different atmospheres - Mahajan, Amit
Carbon nanotubes (CNTs) have unique physical properties. This has been the driver for the current exploitation of their use in different advanced applications, such as in composite nanoscale devices. If a thermal treatment is required for the fabrication of the composite, the thermal decomposition behavior of the tubes is a key aspect in the integration process. Within this context, the thermal decomposition of multiwall CNTs (MWCNTs) under different conditions was studied in this work by DTA/TG, XRD, RAMAN spectroscopy and electron microscopy. Purified MWCNTs are stable up to 420 T in air, as no weight loss occurs in TG/DTA analysis under non isothermal conditions but morphology changes were observed for isothermal conditions at 400 degrees C by Raman spectroscopy. In oxygen-rich atmosphere MWCNTs started to oxidized at 200 degrees C. However in argon-rich atmosphere and under a high heating rate MWCNTs remain stable up to 1300 degrees C with a minimum sublimation. The activation energy for the decomposition of MWCNTs in air was calculated to lie between 80 and 108 kJ/mol. These results have broad implications for the expanded use of MWCNTs in composites with functional complex oxides that usually require synthesis temperature above 650 degrees C. 2012 Elsevier B.V. All rights reserved.